Atendimentos decorrentes de queimaduras em serviços públicos de emergência no Brasil, 2009 Public hospital emergency department visits due to burns in Brazil, 2009 - Vilma Pinheiro Gawryszewski; Regina Tomie Ivata Bernal; Nilza Nunes da Silva; Otaliba Libânio de Morais Neto; Marta Maria Alves da Silva; Márcio Dênis Medeiros Mascarenhas; Naíza Nayla Bandeira de Sá; Rosane Aparecida Monteiro; Deborah Carvalho Malta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
O objetivo foi analisar os atendimentos por queimaduras em serviços de emergência, e fatores associados. Estudo transversal de 761 atendimentos coletados pelo Sistema de Vigilância de Violências e Acidentes em 2009. A maioria foi do sexo masculino (58,6%); adultos de 30 a 49 anos (23,1%) e crianças de 0 a 9 anos (23%). A residência foi o local de ocorrência mais frequente (62,1%), especialmente para crianças e mulheres; em seguida comércio, serviços, indústria e construção (19,1%), especialmente entre homens de 20 a 49 anos. Queimaduras no trabalho foram 29,1% do total. Uso de álcool chegou a 5,1%. Agentes causadores em todas as idades: substância quente (43,6%) e fogo/chama (24,2%); na faixa produtiva: substâncias químicas. As queimaduras entre 0 e 14 anos foram associadas com residência, substância e objeto quente e internação hospitalar; entre os de 15 a 49 anos associaram-se com fogo/chama e choque elétrico, via pública e alta da emergência. Estratégias de prevenção para crianças e trabalhadores devem ser implantadas. The objective was to analyze the characteristics of burn injuries treated in emergency departments (ED) and associated factors. This was a cross-sectional study of 761 ED visits collected through the National Injury Surveillance System in 2009. The majority of patients were males (58.6%), and the most prevalent age brackets were 30-49 years (23.1%) and 0-4 years (23%). Most burns occurred at home (62.1%), especially among females and children, and in commerce/services/industry/construction (19.1%), mainly among males 20-49 years. Work-related burns comprised 29.1% of the overall sample. Alcohol use prior to the injury was reported in 5.1% of cases. Causal agents across all age brackets were: contact with hot substances (43.6%) and exposure to fire and flames (24.2%); among the economically productive age groups, association with chemicals substances was common. Burns in children 0-14 years were associated with injuries at home, contact with heat and hot substances, and subsequent hospitalization; burns in the 15-49-year bracket were associated with exposure to fire/flames and electrical current, injuries occurring in public places, and outpatient treatment and discharge. The study highlights the importance of burn prevention strategies targeting children and workers.